Syphilis and the host: multi-omic analysis of host cellular responses to Treponema pallidum provides novel insight into syphilis pathogenesis - Waugh, Sean; Ranasinghe, Akash; Gomez, Alloysius; Houston, Simon; Lithgow, Karen V.; Eshghi, Azad; Fleetwood, Jenna; Conway, Kate M. E.; Reynolds, Lisa A.; Cameron, Caroline E. (Frontiers in Microbiology, 2023)
Syphilis is a chronic, multi-stage infection caused by the extracellular bacterium Treponema pallidum ssp. pallidum. Treponema pallidum widely disseminates through the vasculature, crosses endothelial, blood-brain and placental barriers, and establishes systemic infection. Although the capacity of T. pallidum to traverse the endothelium is well-described, the response of endothelial cells to T. pallidum exposure, and the contribution of this response to treponemal traversal, is poorly understood. To address this knowledge gap, we used quantitative proteomics and cytokine profiling to characterize endothelial responses to T. pallidum. Proteomic analyses detected altered host pathways controlling extracellular matrix organization, necroptosis and cell death, and innate immune signaling. Cytokine analyses of endothelial cells exposed to T. pallidum revealed increased secretion of interleukin (IL)-6, IL-8, and vascular endothelial growth factor (VEGF), and decreased secretion of monocyte chemoattractant protein-1 (MCP-1). This study provides insight into the molecular basis of syphilis disease symptoms and the enhanced susceptibility of individuals infected with syphilis to HIV coinfection. These investigations also enhance understanding of the host response to T. pallidum exposure and the pathogenic strategies used by T. pallidum to disseminate and persist within the host. Furthermore, our findings highlight the critical need for inclusion of appropriate controls when conducting T. pallidum-host cell interactions using in vitro-and in vivo-grown T. pallidum.